Analisis Hasil Belajar PAI dari Sudut Pandang Tasawuf Sosial: Studi di SMP IT Al-Khairaat Ternate - Murniyati Djufri (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
The moral crisis that occurs in modern times is difficult to contain. One of the facilities that become a forum for shaping the character of the nation's children is through schools, especially through Islamic Religious Education (PAI) subjects. Unfortunately, it is often found that PAI learning is only oriented to the cognitive aspect with various memorization without any meaning and appreciation. Therefore, this article contains research on PAI learning outcomes that were studied using qualitative methods, with a case study design for class IX SMP IT Al-Khairaat City of Ternate. The learning outcomes are then analyzed from the point of view of social Sufism, by looking at aspects of moral, spiritual, and aesthetic orientation. So the results found are a change in better morals, awareness of a sense of responsibility, and reminding each other among students if someone forgets that responsibility. All of this is influenced by the aesthetic method used by the subject teacher when building student character.